Asian slaves in colonial Mexico from Chinos to Indians - Seijas, Tatiana (New York Cambridge University Press, 2015)
"During the late sixteenth and seventeenth centuries, countless slaves from culturally diverse communities in the Indian subcontinent and Southeast Asia journeyed to Mexico on the ships of the Manila Galleon. Upon arrival in Mexico, they were grouped together and categorized as chinos. In time, chinos came to be treated under the law as Indians (the term for all native people of Spain's colonies) and became indigenous vassals of the Spanish crown after 1672. The implications of this legal change were enormous: as Indians, rather than chinos, they could no longer be held as slaves. By tracking these individuals' complex journey from the bondage of the Manila slave market to the freedom of Mexico City streets, Tatiana Seijas challenges commonly held assumptions about the uniformity of the slave experience in the Americas and shows that the history of coerced labor is necessarily connected to colonial expansion and forced global migration"--
1. Catarina de San Juan : China slave and popular saint -- 2. The diversity and reach of the Manila slave market -- 3. The rise and fall of the transpacific slave trade -- 4. Chinos in Mexico City : slave labor and liberty -- 5. Joining the republic of Indians : free Filipinos and freed Chinos -- 6. The Church on chino slaves versus Indian Chinos -- 7. The end of Chino slavery.
Includes bibliographical references (pages 255-272) and index.
Keywords: Enslaved persons -- Mexico -- History; South Asians -- Mexico -- History; Southeast Asians -- Mexico -- History; Enslaved persons -- Legal status, laws, etc. -- Mexico -- History; Slavery -- Mexico -- History -- 16th century; Slavery -- Mexico -- History -- 17th century; HISTORY / Latin America / General; Mexico -- Ethnic relations; Mexico -- History -- 16th century; Mexico -- History -- 17th century